EFEKTIVITAS WEBSITE RECON DALAM MENGURANGI KECEMASAN KARANTINA MANDIRI ORANG DALAM PANTAUAN (ODP) - NAQIY, MUHAMMAD NAMIRUDDIN (Universitas Sahid Surakarta, 2021)
This study aims to determine the effectiveness of mentoringfrrom health volunteer using website Recon (platform tracing odp) to reducing anxiety during self quarantine at home. The research method used pre-experimental one group pre and post test design in which there was only one group that was treated without a control group or other treatment group. The subjects in this study were 5 people in monitoring (ODP) who had anxiety in the moderate to severe category. The treatment given in this research is internetbased assistance and social media. Friedmen test analysis results showed that there were significant differences between pre-test, post-test, and followup to the reduction of anxiety during self quarantine seen from chi square 7,111 with a significance level of 0.029 indicating a significance level smaller than the error rate (p = 0.029, p0.05), the Wilcoxon test results corroborate the hypothesis that anxiety scores persist, post-test scores persist until followup